STUDENTS' ATTITUDES ABOUT CODE-MIXING IN PRACTICING SPEAKING - Humaira , Rizka; Jamaliah; Ramlan (IPI Garut Press, 2024)
Mastering the English language offers numerous opportunities to effectively communicate one's thoughts, feelings, and ideas to a broader audience. Speaking can be difficult because speakers must develop phrases on the spot. This qualitative research aimed to investigate students’ attitudes towards code mixing in spoken language practice through semi-structured interviews. Five students from Jeumala Amal Islamic Senior High School were interviewed as participants because of their frequent use of code-mixing in daily conversations. The results indicated that students' positive attitudes towards code mixing helped them build confidence in speaking English and become more accustomed to using the language as a part of their regular communication habits.